Posturographic Analysis in the Elderly with and without sensorineural Hearing Loss - Ciquinato,Daiane Soares de Almeida (2020)
Abstract Introduction Sensorineural hearing loss (SNHL) is a serious public health problem. Some evidence suggests a significant relationship between SNHL and balance disorders. The inability to maintain balance associated with SNHL while standing further increases the risk of falls among older people. Objective To investigate the association between SNHL on the postural balance in elderly individuals of both genders. Methods The sample consisted of 247 (166 women) physically independent elderly individuals, (mean age = 68.4 ± 6.0). The instruments used were the anamnesis and the pure tone audiometry for hearing loss, and for balance a force platform based in measures of center of pressure area and of sway velocity in the anteroposterior and mediolateral directions. Results Presence of hearing loss (HL) was observed in 68% of the participants. We observed a significant association between SNHL and characteristics of balance between the groups with and without HL for center of pressure (COP) area (p = 0.010), anteroposterior velocity (p = 0.001) and mediolateral velocity (p = 0.020). There was a significant difference between the gender groups for center of pressure area (p = 0.004), anteroposterior velocity (p = 0.001) and mediolateral velocity (p = 0.001) with better performance in the female group. Amongst men, there was a difference between the ones with HL and those without it, for COP area (p = 0.049). Conclusion In the present study, elderly individuals with SNHL exhibited more instability on the postural balance, and elderly men presented worse results in the test.